Imperialism and Religion: Assyria, Judah and Israel in the Eighth and Seventh Centuries B.C. - Gogan, Morton
A Dissertation in Oriental Studies. Presented to the Faculty of the Graduate School of Arts and Sciences of the University of Pennsylvania in Partial Fulfilment of the Requirements for the Degree of Doctor of Philosophy; 14-41: The Assyrian Empire and Foreign Gods; 42-86: Assyrian Spoliation of Divine Images; 87-132: Assyrian Impositions in Provinces and Vassal States.